The equalizer 3 [videorecording (DVD)] - Wenk, Richard; Washington, Denzel, 1954-; Fanning, Dakota, 1994-; Denman, David, 1973-; Girone, Remo, 1948-; Richardson, Robert, 1955-; Zarvos, Marcelo (Sony Pictures Home Entertainment, 2023)
Since giving up his life as a government assassin, Robert McCall has struggled to reconcile the horrific things he's done in the past and finds a strange solace in serving justice on behalf of the oppressed. Finding himself surprisingly at home in Southern Italy, he discovers his new friends are under the control of local crime bosses. As events turn deadly, McCall knows what he has to do: become his friends' protector by taking on the mafia.